ANALISIS PENDAPATAN ORANG TUA DAN HASIL BELAJAR SISWA SMAN 1 SUNGAI RAYA - Sari, Juwita Ika; Witarsa, Witarsa; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is about parents? income analsis and student learning result of class X Social Science on Economics subject at Senior High School 1 Sungai Raya Kabupaten Kubu Raya. This study aims tto determine whether parents? income aects student learning result of class X Social Science on Economics subject at Senior High School 1 Sungai Raya Kabupaten Kubu Raya. This research uses qualitative approach and descriptie researh form. Data collection tools using interiew guidelines.the resuls showed that parents? income can affect student learning outcomes. As many as 9 (nine) students or 60% have parents who have good income and also their children?s good learning outcomes, as many as 2 (two) students or 13,33% whose parents income is low but can show good learning outcomes, as many as 2 (two) students or 13,33% have parents who have good income but the learning result of their children is less, and as many as 2 (two) students or 13,33% have parents who ae low income and the learning result of their children is less. Keywords:     parents? income, learning result, economics subject